Defect engineering boosts ferroelectricity in Pb0.9Ba0.1ZrO3 ceramic. Issue 13 (October 2022) - Liu, Wei; Li, Feng; Long, Mingsheng; Zhai, Jiwei; Wang, Chunchang; Shan, Lei
Abstract: Defect engineering plays a complex role in modulating macroscopic performance in ferroelectric ceramics. Establishing V pb ′ ′ − V o ∙ ∙ defect complex in nitrogen – annealed (NA) Pb0.9 Ba0.1 ZrO3 sample is found to significantly boost ferroelectricity and resistivity and it features a high peak-to-peak strain value ( S p-p 0.132 %), which is 175% larger than that of air – sintered one (Air, S p-p 0.048%). Meanwhile, ferroelectric – recovery effect that found in Air sample is removed for NA. The enlarged lattice strain and resistivity are ascribed to presence of defect complex, as verified by Williamson – Hall analysis and impedance spectra. Guided by Landau free energy analysis, ferroelectric enhancement is due to the presence of charged V pb ′ ′ − V o ∙ ∙ defect complex, which aligns parallel with electric field and thus contributes to defect – complex polarization. This work not only provides an exotic regulation strategy to design fantastic ferroelectric performance by defect engineering and but also enriches understandings of exact nature of defects in bulk ferroelectrics.